Screening for resistance to late blight in wild potato species and landraces in greenhouse conditions in Peru. - Pérez, W.; Rojas, T.; Alarcón, L.; Andrade-Piedra, J.L. (International Potato Center, 2019)
Fifty-seven accessions of wild potato species and 352 accessions of potato landraces hold in the International Potato Center (CIP) were tested for resistance to late blight (LB) in a series of greenhouse experiments from May to December 2018, in Lima, Peru. Wide phenotypic variation for resistance was found within and among species. Six accessions of wild species (Solanum albornozii, S. andreanum, S. lesteri, S. longiconicum, S. morelliforme, and S. stenophyllidium) had more than 60% of genotypes with susceptibility values between 0 to 3. Likewise, 46 of 352 accessions of potato landraces presented similar susceptibility values than those of resistant varieties used as controls. With this study we identified source of resistance to LB to be used by breeders or by farmers directly, in the case of potato landraces. The results confirm the value of conserving potato genetic resources.